A near-continuous record of climate and ecosystem variability in Central Europe during the past 130 kyrs (Marine Isotope Stages 5-1) from Füramoos, southern Germany - Kern, Oliver A.; Koutsodendris, Andreas; Allstädt, Frederik J.; Mächtle, Bertil; Peteet, Dorothy M.; Kalaitzidis, Stavros; Christanis, Kimon; Pross, Jörg (Quaternary science reviews, 2022)
Due to a general scarcity of archives and a lack of temporally highly resolved records, the response of Central European ecosystems to abrupt climate change during the Late Pleistocene - and notably the Last Glacial - has remained insufficiently explored. To contribute to a better understanding of the impact of short-term climate variability on ecosystems in Central Europe north of the Alps during that time, we present a new, near-continuous pollen record from Füramoos, southern Germany. Except for a hiatus from 28 to 20 ka BP, the record spans the past 130 kyrs in centennial-scale resolution. Our pollen dataset is augmented by sedimentological (i.e., XRF core scanning, loss on ignition, and maceral analysis) and macrobotanical data. This new record represents the yet most complete, temporally highest resolved reconstruction of terrestrial ecosystem dynamics in Central Europe for the Last Glacial period. Our results show that temperate forests thrived at Füramoos during full interglacial conditions (i.e., MIS 5e and MIS 1), boreal forests developed during the early glaciation (MIS 5 d-5a), and a tundra vegetation prevailed during full glacial conditions (MIS 4-2). Fourteen transient expansions (contractions) of tree and shrub populations that are synchronous with increases (decreases) in weathering intensity can be firmly attributed to specific Greenland Interstadials (Greenland Stadials) of the NGRIP ice-core record. By comparing individual expansions/contractions of tree and shrub populations with Greenland δ18Oice ice-core and North Atlantic sea-surface temperature (SST) data, we show that during interstadials vegetation dynamics in Central Europe were closely linked to SSTs in the North Atlantic and decoupled from the climate recorded in Greenland; during stadials, the opposite pattern prevailed. We attribute these patterns to changes in AMOC strength and associated latitudinal shifts of the polar front.